Determination of thimerosal in pharmaceutical industry effluents and river waters by HPLC coupled to atomic fluorescence spectrometry through post-column UV-assisted vapor generation - Pacheco, Pablo Hugo (2015)
A high performance liquid chromatography coupled with atomic fluorescence spectrometry method for the determination of thimerosal (sodium ethylmercury thiosalicylate, C9H9HgNaO2S), ethylmercury, and inorganic mercury is proposed. Mercury vapor is generated by the post-column reduction of mercury species in formic acid media using UV-radiation. Thimerosal is quantitatively converted to Hg(II) followed by the reduction of Hg(II) to Hg(0). This method is applied to the determination of thimerosal (THM), ethylmercury (EtHg) and inorganic Hg in samples of a pharmaceutical industry effluent, and in waters of the San Luis River situated in the west side of San Luis city (Middle West, Argentine) where the effluents are dumped. The limit of detections, calculated on the basis of the 3σ criterion, where 0.09, 0.09 and 0.07 μg L−1 for THM, EtHg(II) and for Hg(II), respectively. Linearity was attained from levels close to the detection limit up to at least 100 μg L−1.